Preliminary Phytochemical and Antibacterial studies on Leaf and Bark of Holigarna grahamii (Wight) Kurz. (Anacardiaceae) - Vaibhav Kalase and Varsha Jadhav (Rathod) (Journal of Applied Pharmaceutical Science, 2013)
Holigarna grahamii (Wight) Kurz. is large tree belonging to family anacardiaceae. The bark is smooth and gray in colour, leaves are simple, alternate, glabrous, and midrib is flat. Medicinal plants contribute in human health care system. Most of the plants utilized by village peoples as a folk medicine. Antibacterial activity of the leaves and bark extracts of Holigarna grahamii (Wight) Kurz. against pathogenic bacteria like gram positive (Bacillus subtilis, Staphylococcus aureus) and gram negative (Escherichia coli and Salmonella typhi, Proteus vulgaris) bacteria by in vitro agar well diffusion method. The maximum zone of inhibition of bark extract is observed in Staphylococcus aureus (8.33ï‚±1.15) while in leaves extract it is observed in Escherichia coli (2.66ï‚±0.57). The phytochemical screening of leaf and bark extract shows presence of phenols, tannins, alkaloids and reducing sugar.
Keywords: Antibacterial study, Holigarna grahamii &lt